2006
DOI: 10.1123/jsep.28.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Acute Bout of Exercise on Cognitive Aspects of Stroop Performance

Abstract: Recent reviews of the literature have demonstrated that exercise has a positive impact on cognitive performance. The purpose of this study was to assess the impact of an acute bout of aerobic exercise on executive functioning in college-age adults. For the experimental intervention, the effects of 20 min of self-paced moderate-intensity exercise on a treadmill were compared to the effects of a 20-min sedentary control period. Executive functioning was assessed using Stroop color-word interference and negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
69
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 0 publications
14
69
3
Order By: Relevance
“…The measurement of false alarms is a measure of selective inhibition because irrelevant stimuli must be inhibited in order to decrease the false alarms score. The lack of a condition effect in the current study is similar to other previous research which showed no differences in measures of selective inhibition [13] [19] In contrast to the results from the current study, several studies have shown an improvement between conditions after exercise [9] [20] [21] and Childs and de Wit [7] also saw an improvement in inhibition following the consumption of caffeine. Hogervorst et al [10] also found greater inhibition in a group that received a combination of caffeine and exercise.…”
Section: Discussioncontrasting
confidence: 56%
“…The measurement of false alarms is a measure of selective inhibition because irrelevant stimuli must be inhibited in order to decrease the false alarms score. The lack of a condition effect in the current study is similar to other previous research which showed no differences in measures of selective inhibition [13] [19] In contrast to the results from the current study, several studies have shown an improvement between conditions after exercise [9] [20] [21] and Childs and de Wit [7] also saw an improvement in inhibition following the consumption of caffeine. Hogervorst et al [10] also found greater inhibition in a group that received a combination of caffeine and exercise.…”
Section: Discussioncontrasting
confidence: 56%
“…3,4 Although these reviews indicate that acute exercise has a significant and positive effect on executive function, only a small effect size emerged when considering the global executive function construct that summarized a variety of specific aspects of executive function. Along with the larger effect sizes that are typically observed in empirical studies examining specific aspects of executive function, such as inhibition 11e13, 15,16,46,47 and planning, 6,7,44,51 the findings from these reviews imply that the alterations of sub-components within executive function due to acute exercise are different.…”
Section: Discussionmentioning
confidence: 89%
“…In adults executive functions such as working memory, goal-oriented processing, and inhibition are particularly improved by exercise interventions. 9,10 If this also applies in children, one might expect that the largest effects of exercise would be seen in individuals who have poor executive function, such as those with attention-deficit-hyperactivity disorder. The past 15 to 20 years have seen rapid increases in the diagnosis of this disorder, 11 and this raises the question whether changes in educational practices, such as decreased physical activity, 12 might have contributed to this problem.…”
mentioning
confidence: 99%